Transformation of Korean politics and administration : a 30 year retrospective - Im, Tobin (Public policy and governance., 2022)
Transformation of Korean Politics and Administration: A 30 Year Retrospective retraces critical junctures that were turning points in Korean history as seen from the historical path dependence theory. The 13 chapters explain the significant changes that have occurred in the major pillars of the Korean politics and administration system, helping readers understand the processes of how a 'premodern' society characterized by simplicity became a modern or even post-modern society characterized by multiple and complex operations. This volume gives rich insights to those who are eager to learn lessons from Korea's experiences, provide an additional understanding about temporal dimension of the described events and explore monarchic presidential power, the shifting of power to the legislative branch, the changing role of judiciary branch, government reform strategies, decentralization reform. The Public Policy and Governance series brings together the best in international research on policy and governance issues. Books within the series are authored and edited by experts in the field and present new and insightful research on a range of policy and governance issues across the globe.